A very low-power discrete-time delta-sigma modulator for wireless body area network. (December 2022) - Khoshkam, Z.; Abrishamifar, A.
Abstract: This paper proposes a very low-power discrete-time delta-sigma modulator (DTDSM) for the wireless body area network (WBAN) which deals with biomedical signals. The first stage integrator is optimized using correlated double sampling technique and is implemented using a high-gain designed telescopic operational transconductance amplifier (OTA) in order to maintain the proposed second-order DTDSM high resolution. In order to keep both stage integrators active and prevent ENOB loss, a very low power two-stage charge-steering amplifier is employed in the second stage integrator which leads to a power efficient design. Due to not high but enough voltage-gain of this type of amplifier, the proposed charge-steering-based integrator leads to a negligible loss of ENOB in comparison to passive integrators with no voltage gain which are commonly used in the second stage to reduce the total power. In fact, due to the combination of a high-gain OTA in first stage integrator and a low-power charge-steering amplifier in second stage, compromise between high resolution and low power consumption will be depicted. The proposed DTDSM is designed for a signal bandwidth of 50 kHz with an oversampling ratio of 128 for implantable biomedical devices in the MICS band. Simulations are done using TSMC 180 nm technology at a 1.8 V power supply. Simulation results illustrate that the designed modulator achieves an SNR of 56 dB which is equal to 9 bits of ENOB that is in the desired range for biomedical signals. The power consumption of this modulator is only 142 μW at a 12.5 MHz sampling frequency.